Implantable Electrical Stimulation at Dorsal Root Ganglions Accelerates Osteoporotic Fracture Healing via Calcitonin Gene‐Related Peptide. Issue 1 (28th October 2021) - Mi, Jie; Xu, Jian‐Kun; Yao, Zhi; Yao, Hao; Li, Ye; He, Xuan; Dai, Bing‐Yang; Zou, Li; Tong, Wen‐Xue; Zhang, Xiao‐Tian; Hu, Pei‐Jie; Ruan, Ye Chun; et al.
Abstract: The neuronal engagement of the peripheral nerve system plays a crucial role in regulating fracture healing, but how to modulate the neuronal activity to enhance fracture healing remains unexploited. Here it is shown that electrical stimulation (ES) directly promotes the biosynthesis and release of calcitonin gene‐related peptide (CGRP) by activating Ca 2+ /CaMKII/CREB signaling pathway and action potential, respectively. To accelerate rat femoral osteoporotic fracture healing which presents with decline of CGRP, soft electrodes are engineered and they are implanted at L3 and L4 dorsal root ganglions (DRGs). ES delivered at DRGs for the first two weeks after fracture increases CGRP expression in both DRGs and fracture callus. It is also identified that CGRP is indispensable for type‐H vessel formation, a biological event coupling angiogenesis and osteogenesis, contributing to ES‐enhanced osteoporotic fracture healing. This proof‐of‐concept study shows for the first time that ES at lumbar DRGs can effectively promote femoral fracture healing, offering an innovative strategy using bioelectronic device to enhance bone regeneration. Abstract : Electrical stimulation (ES) at dorsal root ganglions (DRGs) triggers calcium influx and activates the Ca 2+ /CaMKII/CREB signaling cascade, resulting in the transcription of calcitonin gene‐related peptide (CGRP). After synthesized in DRGs, CGRP is transported to peripheral nerve terminals and released following depolarization by ES. The released CGRP and subsequently increased type‐H vessel formation promote osteoporotic fracture healing.